2006
DOI: 10.2202/1524-5861.1130
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Direct Investment and Economic Growth: A Time-Series Approach

Abstract: Research has often focused on how foreign direct investment (FDI) transfers technology from developed economies to less developed economies. Most FDI occurs between developed economies, however, and the country receiving the greatest inflow of FDI is the United States. This paper examines whether such FDI inflows have stimulated growth of the U.S. economy. We apply time-series data to a simultaneous-equation model (SEM) that explicitly captures the bi-directional relationship between FDI and U.S. economic grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 56 publications
0
4
0
2
Order By: Relevance
“…The positive relationship between FDI at the aggregate level, and real income per capita, was found by Khawar (2005). Roy & Berg (2006) revealed that even an industrially advanced country benefits from FDI, and the gains from FDI are significant in the long run. Behname's (2012) study shows that FDI has a positive effect on Southern Asia's economic growth and that human capital, trade, economic infrastructure, and capital had a positive effect on attracting FDI.…”
Section: Literature Reviewmentioning
confidence: 96%
“…The positive relationship between FDI at the aggregate level, and real income per capita, was found by Khawar (2005). Roy & Berg (2006) revealed that even an industrially advanced country benefits from FDI, and the gains from FDI are significant in the long run. Behname's (2012) study shows that FDI has a positive effect on Southern Asia's economic growth and that human capital, trade, economic infrastructure, and capital had a positive effect on attracting FDI.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Overseas direct investment on the growth driving element for the budget was mentioned by many studies such as Ghosh and Van den Berg (2006) and Iqbal et al (2010). An important issue that most of developing economies suffer is gap in savinginvestment and overseas direct investment limits this cavity by improving the output, recent expertise, producing opportunities for youth while also enhancing the competition (Kobrin, 2005).…”
Section: Existing Review Of Literaturementioning
confidence: 99%
“…Carkovic and Levine (2002) found no significant effect in either developed or developing countries for the period 1960-1995. Roy and Von den Berg (2006) examined the impact of foreign direct investment on economic growth in the United States. According to the results, there is a significant and positive relationship between FDI and U.S. economic growth.…”
Section: F Ebghaeimentioning
confidence: 99%